DIOCTOPHYMA RENALE: RELATO DE CASO - Dassow, Talisa Cristine; Weiss, Larissa Koslowski; Gelain, Milena Rossi; Conrad, Marjane Altíssimo; Da Veiga, Daniela Caroline; Inkelmann, Maria Andréia (Salão do Conhecimento, 2019)
Relato de caso